A Detailed Study of Irradiation Requirements Towards an Efficient Photochemical Wohl‐Ziegler Procedure in Flow. Issue 10 (19th June 2018) - Bonfield, Holly E.; Williams, Jason D.; Ooi, Wei Xiang; Leach, Stuart G.; Kerr, William J.; Edwards, Lee J.
Abstract: A platform has been developed to enable standardization of light sources, allowing consistent scale‐up from high‐throughput screening in batch to flow, using the same pseudo‐monochromatic light source. The impact of wavelength and light intensity on a photochemical reaction was evaluated within this platform using the Wohl‐Ziegler benzylic bromination of 4‐methyl‐3‐(trifluoromethyl)benzonitrile with N ‐bromosuccinimide as a model system. It was found that only 40 % of the maximum light intensity was required while still maintaining reaction rate, allowing more reliable temperature control and lower energy consumption. The optimized reaction conditions were subsequently applied to a range of synthetically relevant (hetero)aromatic compounds under continuous conditions, exploring the scope of the process within a mild and scalable procedure. Abstract : And then there was light : The significance of defining light power requirements within photochemical reactions has been exemplified using the Wohl–Ziegler reaction in batch and flow. The optimized reaction conditions were subsequently applied to a range of synthetically relevant (hetero)aromatic compounds under continuous flow conditions.